International financial institutions and international public goods : operational implications for the World Bank - Kanbur, Ravi (UN New YorkUS, 2002)
Defines International Public Goods (IPGs) and characterizes their key dimensions. Discusses World Bank practice for specific IPGs. Considers reforms in order to better articulate the comparative advantage of the Bank with the requirements of IPG provision.